Assessing the visual afferent pathway with the multifocal visual evoked potentials in the radiologically isolated syndrome - M. Roldán; N. Caballé; C. Sainz; C. Pérez-Rico; L. Ayuso; Roman Blanco (Scientific Reports, 2024)
Abstract The early identification of individuals with radiologically isolated syndrome (RIS) who are at an elevated risk of progressing to multiple sclerosis (MS) is essential for making informed treatment decisions. This study aimed to evaluate the predictive potential of multifocal Visual Evoked Potentials (mfVEP) measures in individuals with RIS with respect to their conversion to MS. A prospective observational cohort study was conducted, involving 21 individuals with RIS recruited from a MS center. Baseline assessments, including mfVEP, magnetic resonance imaging (MRI), and clinical examinations, were performed, and participants were longitudinally followed for up to 24 months. The primary outcome measures were the conversion to MS. Over a clinical follow-up period of 24 months, five individuals (5/21) with RIS progressed to MS. MfVEP amplitude responses (interocular and monocular probability analysis) demonstrated abnormal cluster visual field defects in 47.6% of RIS eyes at baseline, whereas multifocal VEP latency analysis showed significant delays in 38.4%. A reduction in interocular amplitude [OR = 0.036, (95% CI 0.003–0.503); P = 0.014], monocular amplitude [OR = 0.083, (95% CI 0.007–0.982); P = 0.048], and a prolonged interocular latency [OR = 0.095, (95% CI 0.009–0.972); P = 0.047] were associated with a higher relative risk of clinical conversion at the 2-year follow-up. Multifocal VEP may serve as a novel and independent risk factor for predicting the conversion to MS in individuals with Radiologically Isolated Syndrome.